2013
DOI: 10.1002/j.2161-1874.2013.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Addiction Competencies in the 2009 CACREP Clinical Mental Health Counseling Program Standards

Abstract: The Council for Accreditation of Counseling and Related Educational Programs developed addiction competencies for clinical mental health counseling students. This article highlights these competencies, provides an overview of current addiction training, and describes methods to integrate addiction education into curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The healthcare field at large lacks formal substance misuse training in educational programs (Gotham et al, 2015). However, while other mental health fields have already critically examined the extent of substance misuse–related curriculum in their training programs (Corbin et al, 2013; Lee et al, 2013; Quinn, 2010), the C/MFT field has lagged behind. This study explored substance misuse training among C/MFTs to identify gaps in training and better understand how to enhance substance misuse training in graduate programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The healthcare field at large lacks formal substance misuse training in educational programs (Gotham et al, 2015). However, while other mental health fields have already critically examined the extent of substance misuse–related curriculum in their training programs (Corbin et al, 2013; Lee et al, 2013; Quinn, 2010), the C/MFT field has lagged behind. This study explored substance misuse training among C/MFTs to identify gaps in training and better understand how to enhance substance misuse training in graduate programs.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers from other mental health disciplines, including psychology, social work, and counseling, have specifically examined how well their respective fields are preparing clinicians to work with substance misuse issues, and all these disciplines have identified the importance of formal clinical training in this area (Corbin et al, 2013; Lee et al, 2013; Quinn, 2010). However, to date, there is no research that examines the existence and extent of substance misuse training for C/MFTs.…”
Section: C/mft Substance Misuse Training Elementsmentioning
confidence: 99%
“…The emphasis placed on curricular developments during this time period is not surprising given the introduction and transition to the 2009 CACREP Standards. Lee, Craig, Fetherson, and Simpson () suggested that more research is needed to assist counselor educators in incorporating addiction instruction into counselor training curricula. The frequency of addiction‐related counselor education and supervision research may increase further given the recent emphasis by JAOC to publish research related to competency‐based training in addiction counseling (Southern, ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, the Council for Accreditation of Counseling and Related Educational Programs (CACREP) added addiction counseling to the CACREP program options (CACREP, ). The 2009 accreditation standards also included the development of addiction competencies for other specialty tracks, as well as the integration of addiction education into the common core curricular experiences (Lee, Craig, Fetherson, & Simpson, ; Moro, Wahesh, Likis‐Werle, & Smith, ). Prior to the transition to 2009 accreditation standards, graduates from CACREP‐accredited programs may not have received any education in addiction counseling.…”
Section: Addiction Counseling Trainingmentioning
confidence: 99%
“…ricular experiences (Lee, Craig, Fetherson, & Simpson, 2013;Moro, Wahesh, Likis-Werle, & Smith, 2016). Prior to the transition to 2009 accreditation standards, graduates from CACREP-accredited programs may not have received any education in addiction counseling.…”
mentioning
confidence: 99%